Drying kinetics and determination of the effective diffusion coefficient of noni and umbu pulps (Research, Society and Development, 2021)
Noni (Morinda citrifolia L.) and umbu (Spondias tuberosa Arruda Câmara) are still little-known fruits with industrial exploitation at an incipient level. To preserve production, when not consumed as soon as harvested, it is necessary to subject them to processing, including cooling or drying in order to keep them in conditions suitable for consumption. In view of this, the objective of this work was to evaluate the drying kinetics of the combined pulps of noni with umbu at temperatures of 40, 50, 60 and 70 ° C, to adjust mathematical models to describe the process, as well as to determine their thermodynamic properties. For each temperature, 200g of combined pulp were used, dried by convection in an oven with forced air circulation, in triplicate. The humidity ratios were calculated and the mathematical models of Page, Henderson and Pabis, Logarithmic and Newton were adjusted for each temperature. The increase in the temperature of the drying air reduced the time needed to remove water from the combined pulps of noni and umbu. The Page model showed the highest value of the adjusted coefficient of determination (> 0.99) and the lowest value of the mean square deviation (